Regional Energy Master Plan based on Low Emission Scenarios: Case Study of Central Java Province, Indonesia - Setiartiti, Lilies; Rachmawatie, Dessy (Jurnal Ekonomi & Studi Pembangunan, 2022)
The current energy crisis momentum is the right time to redesign energy policy; otherwise, the energy deficit will continue and influence economic activities. For this reason, this research took Central Java Province as a case study. This research aims to estimate energy demand, the dominance of energy use, and energy efficiency. In this study, energy demand was modeled by sector using the intensity approach to calculate the energy used per activity unit. Low Emissions Analysis Platform (LEAP) model was then utilized to figure out future trends in energy demand and energy structure from 2015 to 2030 under different scenarios, including Business as Usual (BAU), Moderate (MOD), and Optimistic (OPT) scenarios. The results uncovered that energy demand in Central Java has grown by 5.6% per year, and the overall final energy demand is 1,683,091.24 thousand BOE. In this case, the transportation and household sectors are the largest and second-largest consumers, while premium and electricity are the dominant components in this province. In addition, efficiency energy could be achieved in 2021 and 2017, respectively, under the MOD and OPT scenarios. From the utilization of renewable energy, Central Java also contributes 1.17% to the utilization of renewable energy nationally. Overall, this research provides important insights and highlights possible steps for policymakers in developing energy efficiency policies.